Optimalisasi Pemanfaatan Pekarangan Rumah Sebagai Peluang Bisnis Keluarga - Kusumastuti, Anggit Dyah (Bhinneka Publishing, 2022)
Utilization of the yard is the first step to stimulate the growth of the spirit of self hap and community participation. Mina Surya is one of a group of young entrepreneurs whohave the entrepreneurial spirit to change their mindset by optimizing the local potential around them through the use of home yards that can be developed into valueable commodities. The form of utilization carried out by Mina Surya is a private pool tourism object and aquaculture business as a family run business opportunity. Mina Surya is a young entrepreneur from Jeblog, Karanganom, Klaten who has a set of konwledge and skills (life skills) in the field of fisheries so as to develop local potential by optimizing the use of home yard land to become a private poll tourism object and aquaculture as a family business opportuniy.